Information and Communication Technologies in Education, Research, and Industrial Applications 9th International Conference, ICTERI 2013, Kherson, Ukraine, June 19-22, 2013, Revised Selected Papers - Ermolayev, Vadim; Mayr, Heinrich C.; Nikitchenko, Mykola; Spivakovsky, Aleksander; Zholtkevych, Grygoriy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 9th International Conference on Information and Communication Technologies in Education, Research, and Industrial Applications, held in Kherson, Ukraine, in June 2013. The 18 revised full papers presented were carefully reviewed and selected from 125 submissions. The papers are organized in topical sections on systems, infrastructures, and integration; semantics, knowledge engineering and management; ICT in teaching methodologies and didactics; model-driven software development and verification.
Systems, infrastructures, and integration -- Semantics, knowledge engineering and management -- ICT in teaching methodologies and didactics -- Model-driven software development and verification.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Education; Computer Science; Computers and Education; Software Engineering; Logics and Meanings of Programs; Artificial Intelligence (incl. Robotics).